Assessing Emergency Animal Safe Sites for Evacuation. Issue 2 (1st November 2022) - Ogunmakinde, O E; Egbelakin, T; Henderson, R
Abstract: Providing shelters for animals during disasters such as floods, bushfires and storms requires adequate planning and preparedness. Planning for animals during the disaster response and recovery phases is critical to mitigating the negative effects that animal loss or separation can have. The human-animal bond has the potential to influence people's decisions during emergencies, such as how they will respond and when or if they will evacuate. Evacuation with animals during a disaster event can be difficult and complicated. It is critical, however, that animals are rescued and kept safe during and after disasters. Any compromise can result in the death of such animals. Similarly, even in disaster-related situations, animal handling should be consistent with the Australian Animal Welfare Standards and Guidelines. This project aims to better understand disaster preparedness and resilience, as well as the recovery of animals during a disaster event. Twenty-five potential animal evacuation sites, including saleyards, showgrounds, animal shelters, and racecourses, were identified and accessed in nine local government areas (LGAs) across the Hunter region of New South Wales, Australia. On-site survey using a 5-point Likert scale questionnaire was used to collect data. While none of the facilities are of high standard, 16% would require cosmetic work, 76% would require minor work, and the remaining facilities would require significant work. The project's implication is that the assessment guideline can be included in the local council's emergency management plan to improve adequate planning for safe animal evacuation.